2019
DOI: 10.3390/polym11030387
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Thermodynamic Model for Transport Properties of Thin Films during Physical Aging

Abstract: A coupled diffusion model based on continuum thermodynamics is developed to quantitatively describe the transport properties of glassy thin films during physical aging. The coupled field equations are then embodied and applied to simulate the transport behaviors of O2 and CO2 within aging polymeric membranes to validate the model and demonstrate the coupling phenomenon, respectively. It is found that due to the introduction of the concentration gradient, the proposed direct calculating method on permeability c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It is an inherent property that is temporary and variable, where the polymer′s physical state and density significantly affect its value. The mechanism of reducing the extra free volume of the membrane can be linked to physical aging, arising from the contraction of the lattice and the migration and diffusion of the free volume from the inside of the membrane to the surface [ 32 ]. These explanations reveal the importance of the polymer structure in the kinetics of the drug release.…”
Section: Resultsmentioning
confidence: 99%
“…It is an inherent property that is temporary and variable, where the polymer′s physical state and density significantly affect its value. The mechanism of reducing the extra free volume of the membrane can be linked to physical aging, arising from the contraction of the lattice and the migration and diffusion of the free volume from the inside of the membrane to the surface [ 32 ]. These explanations reveal the importance of the polymer structure in the kinetics of the drug release.…”
Section: Resultsmentioning
confidence: 99%
“…For an ASSB with time-aging SPE, as the essence of the time-aging of SPE is the process of free volume escaping outward [ 18 , 19 , 20 ], it can be expected that the time-aging would result in not only the decline of ion migration in the electrolyte but also the decrease in bulk volume of SPE because of the polymer densification induced by the aging process. As a result, changes in cutoff time and contact area caused by aging may affect the electrochemical performance of the ASSB.…”
Section: Methodsmentioning
confidence: 99%
“…Tian and Qi have found that contact loss formed during cell fabrication resulted in degradation of the battery performance [ 17 ]. The imperfect contact may be worsened during the physical aging process, where excess free volumes progressively escape from the polymer-lithium salt system due to a naturally occurring densification of the polymer structure [ 18 , 19 , 20 ]. Although the physical aging-induced SPE volume decrease may reduce the contact area of electrolyte/electrode interface and correspond to the electrical properties, up to now, no previous studies have paid close attention to the effect of time-aging on the interfacial contact between the solid electrolyte and electrode.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to a rapid solvent volatilization or the steep cooling from melting temperature in the process of solidification, all of above amorphous or semi-crystalline polymers are inevitably in the high nonequilibrium state. The electrolyte material with excess thermodynamic quantities would spontaneously evolve with time to equilibrium, which is referred to as physical aging [ 34 , 35 ], leading to pronounced variations in the microstructure and also macroscopic properties under storage and servicing operations. Accordingly, the physical aging process of SPEs and its effects on ASSB performance is a pivotal scientific problem to be solved.…”
Section: Introductionmentioning
confidence: 99%